Research activities of the Nuclear Graphite Research Group - University of Manchester - Marsden, B; Fok, A; Marrow, J; Mummery, P (2004)
In 2001, the Nuclear Safety Division (NSD) of the UK Health and Safety Executive (HSE) decided to underwrite the Nuclear Graphite Research Group (NGRG) at the University of Manchester, with the aim of providing a source of independent research and advice to the HSE (NSD). Since then, the group has rapidly expanded to sixteen members and attracted considerable funding from the nuclear power industry and the regulator for a wide-range of research and consultancy work. It is now also part of the Material Performance Centre within the BNFL Universities Research Alliance. Extensive collaboration exists between the group and other nuclear research institutes, both in the UK and overseas. This paper briefly describes some of the research programmes being carried out by the NGRG at Manchester.